2005
DOI: 10.1074/jbc.m504530200
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling the Chemical Steps of Telomere Resolution by ResT

Abstract: ResT is the telomere resolvase of the spirochete Borrelia burgdorferi, the causative agent of Lyme disease.ResT is an essential cellular function that processes replication intermediates to produce linear replicons terminated by covalently closed hairpin telomeres. ResT generates these hairpin telomeres in a reaction with mechanistic similarities to those catalyzed by type IB topoisomerases and tyrosine recombinases. We report here, that like most of the tyrosine recombinases, ResT requires interprotomer commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…5). This does not occur easily on linear or relaxed DNA (25,32,34). Once this has occurred, DNA cleavage and hairpin formation rapidly follows, all within the context of the cross-axis complex (this study).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…5). This does not occur easily on linear or relaxed DNA (25,32,34). Once this has occurred, DNA cleavage and hairpin formation rapidly follows, all within the context of the cross-axis complex (this study).…”
Section: Discussionmentioning
confidence: 93%
“…Our previous report that studied telomere resolution with substrates that blocked cleavage or hairpinning on one side of an rTel indicated that the chemical steps of telomere resolution could be uncoupled from each other (32). For the hairpin formation step of the reaction, this was particularly surprising as it implied that a hairpin telomere would be produced at the expense of also producing a deleterious ResT-capped double strand break.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At this writing telomere resolvases have been purified from three phage and seven bacterial species: E. coli phage N15 (3), Klebsiella oxytoca phage φKO2, Yersinia enterocolitica phage PY54 (5), Agrobacterium tumefaciens (8), the Lyme spirochete Borrelia burgdorferi (6), the relapsing fever borreliae B. hermsii, B. parkeri, B. recurrentis, B. turicatae, and the avian spirochete B. anserina (7). The B. burgdorferi enzyme, ResT (Resolvase of Telomeres) has been the most extensively studied at the biochemical level (6,7,10,11,12,13,14,15,16,17,18,19,20,21,22,23) and is the primary focus of this review, with properties of the other enzymes noted (3,4,5,8,24). Structural studies of the Klebsiella phage φKO2 (25) and the Agrobacterium (26) resolvases have been reported and have shed additional light on reaction mechanisms and on differences between the resolvases from different organisms.…”
Section: Hairpin Telomere Resolvasesmentioning
confidence: 99%